2021
DOI: 10.3390/pr9112061
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of PEM Fuel Cells with an Additional Outlet in the Parallel Flow Field

Abstract: The design of bipolar plates is critical for improving the performance of proton exchange membrane fuel cells (PEMFCs). In this research, a new additional outlet based on a PEMFC’s parallel flow field was proposed, and three different positions of outlet were designed on the target side of gas flowing in parallel channels. The results revealed that the additional outlets are able to increase the gas speed through channels near the additional outlets, which results in a lower water saturation and a more uniform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It exhibits the worst performance among the anode flow‐field plates applied in this study. The increases in power and current densities are also lower than those of the other flow‐field plate designs, because the glucose solution does not reach the entire flow path, owing to the characteristics of the parallel flow path, and it is difficult to disperse because of the low differential pressure [11,51,52] . Consequently, even if the channel width is increased, the performance is low because the glucose permeability is not sufficiently improved.…”
Section: Resultsmentioning
confidence: 96%
“…It exhibits the worst performance among the anode flow‐field plates applied in this study. The increases in power and current densities are also lower than those of the other flow‐field plate designs, because the glucose solution does not reach the entire flow path, owing to the characteristics of the parallel flow path, and it is difficult to disperse because of the low differential pressure [11,51,52] . Consequently, even if the channel width is increased, the performance is low because the glucose permeability is not sufficiently improved.…”
Section: Resultsmentioning
confidence: 96%
“…The total number of elements is 893000 with a minimum orthogonality of 0.6169546. According to the paper (Zhang et al, 2021), where the dependence of the results on the mesh density was examined for a full fuel cell, not only for one channel, it is indicated that the number of 707556 mesh elements is sufficient. In this work, 893000 elements were obtained for only one channel.…”
Section: Geometric Modelmentioning
confidence: 99%
“…In addition, its function as an energy carrier, its storability can be exploited to meet the requirements set by energy consumers [4]. The fuel cells emerge as the missing link by transforming chemical energy into electrical energy with high efficiency [5]. Hence, they use the chemical energy of hydrogen and oxygen to generate electricity without pollution, and the other products are just plain water, and heat [6].…”
Section: Introductionmentioning
confidence: 99%